Innovation and Utilization of FABA Bean Waste as Briquette Material: A Study on Combustion Characteristics - maysharah sambo; Nofriady Handra (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2025)
This study aims to investigate the innovation and utilization of fly ash bottom ash (FABA) waste from PLTU Ombilin as a briquette material, focusing on its combustion characteristics. FABA, a by-product of coal combustion, poses environmental challenges if not properly managed. In this research, FABA was blended with pyrolyzed pecan shells and starch as a binding agent, then compacted into briquettes with varying compositions. The combustion characteristics, including ignition time, combustion temperature, and calorific value, were evaluated using standard testing methods. The results indicate that variations in raw material composition significantly influence briquette performance. Briquettes containing 70% FABA, 20% pecan shell, and 10% starch exhibited the longest ignition time of 4 minutes and 3 seconds, with an average combustion temperature of 243°C. Meanwhile, briquettes composed of 60% FABA, 30% pecan shell, and 10% starch achieved the highest average combustion temperature of 376°C, with a flame duration of 3 minutes and 34 seconds. The highest calorific value, 8,714 cal/g, was obtained from briquettes containing 40% FABA, 10% pecan shell, and 40% starch. These findings demonstrate the potential of FABA waste as an alternative fuel source and contribute to sustainable industrial waste management and the development of environmentally friendly energy materials.